자동차 차체의 점 용접을 위한 용접건의 자세 범위 자동 계산 - 김연수(Yeonsu Kim); 손충일(Chungil Son); 만예동(Ruidong Man); 정융호(Yoongho Jung) (한국CDE학회 논문집, 2021)
Car bodies need a large number of spot welding for lightweight and rigid bonding. Before the spot welding process, the posture of the selected weldgun must be reviewed first not to interfere with the welding objects and fixtures. A commercial CAD program can automatically calculate the posture range of a weldgun, but it takes too much time for use in the car industry. This study developed a method with a program to review the weldability automatically within an acceptable time. For the versatility of the developed program, the welding target and weldgun data are input in STL format that is a standard for CAD models. However, it does not provide any topology information of the models, which makes it difficult to get the necessary welding information. After getting the welding information, this study developed an algorithm to calculate the range of weldable posture of a weldgun within a few seconds by the Octree and the CPU parallel processing method. The proposed method can be applied not only to the automobile but also to spot welding processes in other fields. KCI Citation Count: 0